PENGARUH IRADIASI TERHADAP KUALITAS SAMBAL TRADISIONAL (Irradiation Effect on The Quality of Traditional Sauce) - Kadir, Idrus (Jurnal Hasil Penelitian Industri, 2014)
Research on the application of irradiation technology in the field of foodpreservation has done relatively long which began around the 1950s to the present . Oneof the benefits of irradiation technology as an alternative technology for food preservationis not causing residue and can maintain the quality of foodstuffs including nutritionalquality remained relatively unchanged. Research on the effect of irradiation on the qualityof traditional sauce has been done. Tradisional sauce obtained from one of thesupermarkets in South Jakarta were irradiated with doses of 5 kGy and 0 kGy as controls .Three brands of traditional sauce on the market are brands A , B and C which have beenprepared in packaging bag included in the carton at a certain size and then irradiated at adose of 5 kGy , and the sauce is not irradiated ( control ) was prepared for comparison . Atboth the irradiated sauce and unirradiated as control were tested those fisico-chemistryand microbiology quality namely: pH , water content , water activity ( Aw ), protein content,fat content total microbial ( ALT ), molds and yeasts , total coliforms , and Staphylococcusaureus . In the control (0 kGy), conducted testing heavy metal. The results showed thatirradiation can improve the hygienic quality of traditional sauce by reducing microbialcontamination 2-3 log cycle at a dose of 5 kGy . In the traditional sauce found nosignificant heavy metal contamination. Improved hygienic quality of traditional saucethat expected to increase the competitiveness of agro- industry of traditional sauce inorder to boost the economy.